PENDIDIKAN AKHLAK BERBASIS AL-QUR’AN: ANALISIS NILAI-NILAI MORAL DALAM PERSPEKTIF TAFSIR TARBAWI - Ayub Kumalla; Burhanudin Khairi; Ainal Ghani; Muhammad Akmansyah; Amirudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the values of moral education contained in the Qur’an as a fundamental guide for shaping human character. The research aims to describe the concept of moral education (akhlak), clarify its objectives, and analyze Qur’anic verses relevant to moral development, particularly QS. Ali Imran:159, QS. Al-Hujurat:11, and QS. An-Nisa:148. This study employs a qualitative library research method by analyzing classical and contemporary tafsir sources as well as references related to Islamic education. The findings reveal that moral education in the Qur’an emphasizes noble character, including compassion, gentleness, mutual respect, avoidance of mockery, and refraining from speaking ill of others. These values play a crucial role in shaping individuals who are pious, responsible, and socially ethical. Furthermore, the Qur’an highlights moral principles as the foundation of societal harmony, where strong moral character contributes to the rise of a community, while moral decay leads to its decline. The study concludes that moral education must be implemented consistently through family, schools, and society to develop holistic individuals with strong spiritual and social integrity.